MENANAMKAN KARAKTER OPTIMIS DENGAN PERMAINAN TRADISIONAL PADA ANAK USIA 7-9 TAHUN - Brigita Pundi Novena; Gregorius Ari Nugrahanta (UNIKU PRESS, 2022)
The lack of character education, especially optimism, caused problems, one of which was cheating. Optimistic character sounded foreign to early childhood, especially the lack of implementation of optimistic character education was lacking. Therefore, this studied aims to develop a traditional game manual to cultivate optimistic characters in children aged 7-9 years. The addie typed researched and development (rd) model was used as a method in this studied. Ten certified teachers from various regions was involved in this researched for needed analysis, ten validators for expert judgment, and eight children was involved in a limited trial. The results of this studied indicate that (1) the analysis of optimistic character needed shows an average of 2. 06 classified as